Src interacts with TRAF5 and promotes NF-κB-associated antiviral responses against iridovirus in marine teleost - Lingfeng Guan; Yi Li; Ting Yu; Jiamei Long; Runchang Zhou; Zhifeng Chen; Hua Huang; Jinglin Tan; Min Yang; Shaowen Wang; Qiwei Qin (Fish & Shellfish Immunology, 2026)

Morinda officinalis polysaccharide improves osteoporosis by enhancing m⁶A-modified SOCS5 mRNA stability via regulating the hsa_circ_0001165/IGF2BP2 axis - ZhiBo Zhu; Yi Yang; Yi Liu; LingFeng Liao (Molecular Genetics and Genomics, 2026)

Advancing analysis of biofuel precursors from lignin: complete molecular characterization using GC × GC-FID - Linyu Zhu; Miloš Auersvald; Cunhao Cui; Yuhe Liao; Jing Zhang; Qing He; Lingfeng Li; Yi Ouyang; Zhongyue Zhou; Fei Qi; Kevin M. Van Geem (Fuel, 2026)

Strongly coordinating anions and cosolvent synergy enabled lithium metal batteries - Yutao Liu; Yi Li; LingFeng Zhang; Mengmeng Tan; QiXian Zhang; Wei Lü (Chemical Engineering Journal, 2026)

Clinical efficacy and mechanistic study of intrauterine administration of E bing angong Ye for the treatment of endometritis in sows - Yi-Meng Fan; Xinyi Zhou; Lu Wang; Xiyu Wen; Xueyan Wang; Lingfeng Peng; Luyao Wang; Zhihui Hao (Theriogenology, 2026)

Polystyrene microplastics impede growth and induce behavioural toxicity in endangered juvenile horseshoe crabs (Tachypleus tridentatus) - Yi Jiang; Zhiyuan Yang; Lingfeng Jiang; Cheong-Meng Chong; Shanza Gul; Youji Wang; Khor Waiho; Xiaowan Ma; Zhi Chen; Menghong Hu (Marine Environmental Research, 2026)

Community assembly and nitrogen metabolic characteristics of size-fractionated microorganisms in floating bed restoration area - Yi Shi; Rui Zhao; Lingfeng Huang; Wenjing Zhang (Journal of Oceanology and Limnology, 2026)

A multiscale generative adversarial network approach for generating porous media with structural morphology - Yafei Xu; Lingfeng Guo; Danqing Song; Yi Shan; Xiaoli Liu (Stochastic Environmental Research and Risk Assessment, 2025)

High-throughput screening and inhibition mechanism analysis of Bacillus licheniformis BL-4 as an antagonistic strain for Lactobacillus panis - Lingfeng Yi; Xinyue Li; Menglin She; Yaokang Wu; Jianghua Li; Guocheng Du; Long Liu; Li Wang; Yanfeng Liu (Systems Microbiology and Biomanufacturing, 2025)

Targeting Nrf2 by bioactive peptides alleviate inflammation: expanding the role of gut microbiota and metabolites - Zhongxing Chu; Lingfeng Zhu; Yaping Zhou; Feiyan Yang; Zuomin Hu; Yi Luo; Wen Li; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2025)

A unimodal soil-water characteristic curve model for gap-graded soil based on bimodal grain-size distribution and fractal theory - Yuefeng Wu; Junsheng Chen; Weidong Pan; Lingfeng Guo; Yi Shan (Transportation Geotechnics, 2025)

Saline seepage circulation experiment study on low plastic limit clays combined with microscale tests and the fractal theory - Lingfeng Guo; Yingguang Fang; Yafei Xu; Renguo Gu; Shufeng Bao; Yi Shan (Bulletin of Engineering Geology and the Environment, 2024)

Targeting gut-brain axis by dietary flavonoids ameliorate aging-related cognition decline: Evidences and mechanisms - Zhongxing Chu; Shuai Han; Yi Luo; Yaping Zhou; Lingfeng Zhu; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2024)

Doped microspheres for whispering gallery mode microlasing - Xiaoxuan Wang; Chaoyang Huang; Chuansheng Xia; Feifei Qin; Gangyi Zhu; Lingfeng Mao; Yi Ma; Zengliang Shi; Qiannan Cui; Chunxiang Xu (Science Bulletin, 2024)

Recent advances on environmental behavior of Cu-based nanomaterials in soil-plant system: A review - Jieyu Gao; Yi Zhu; Lingfeng Zeng; Xin Liu; Yuan Yang; Yaoyu Zhou (Journal of Environmental Management, 2024)

Mitogenomic phylogeny of Muricidae (Gastropoda: Neogastropoda) - Yi Yu; Lingfeng Kong; Qi Li (Zoologica Scripta, 2023)
Muricidae is one of the most species‐rich and morphologically diverse families in Gastropoda, with a worldwide distribution. The classification of Muricidae has traditionally been based on shell and radular characteristics; however, the phylogenetic relationships within the family are debated due to morphological convergence and plasticity. In this study, to explore the phylogenetic relationships of Muricidae, we sequenced 11 muricid mitochondrial (mt) genomes and compared them with 13 previously reported complete muricid mt genomes. All muricid mt genomes shared the same gene arrangement and exhibited conserved genome size and nucleotide composition. Three‐nucleotide deletions in atp8 and nad4 , and three‐nucleotide insertions in nad2 were detected in Rapaninae. Both maximum likelihood and Bayesian inference analyses supported the monophyly of each subfamily studied (Ocenebrinae, Muricinae, Rapaninae and Ergalataxinae). Ergalataxinae was recovered as the sister taxon of Rapaninae, refuting the traditional morphology‐based placement of Ergalataxinae within Rapaninae. In Rapaninae, Indothais was confirmed to be monophyletic and determined to be a valid genus. Similarly, Drupina was determined to be an independent genus rather than a subgenus of Drupa . Purpura was recovered as a paraphyletic group, with Purpura panama being sister to Reishia + Rapana + Indothais and clustering with Purpura bufo .

Phylogenomic resolution of Imparidentia (Mollusca: Bivalvia) diversification through mitochondrial genomes - Yu Wang; Yi Yang; Lingfeng Kong; Takenori Sasaki; Qi Li (Marine Life Science & Technology, 2023)
Despite significant advances in the phylogenomics of bivalves over the past decade, the higher-level phylogeny of Imparidentia (a superorder of Heterodonta) remains elusive. Here, a total of five new mitochondrial sequences ( Chama asperella , Chama limbula , Chama dunkeri , Barnea manilensis and Ctena divergens ) was added to provide resolution in nodes that required additional study . Although the monophyly of Lucinida remains less clear, the results revealed the overall backbone of the Imparidentia tree and the monophyly of Imparidentia. Likewise, most relationships among the five major Imparidentia lineages—Lucinida, Cardiida, Adapedonta, Myida and Venerida—were addressed with a well-supported topology. Basal relationships of Imparidentia recovered Lucinidae as the sister group to all remaining imparidentian taxa. Thyasiridae is a sister group to other imparidentian bivalves (except Lucinidae species) which is split into Cardiida, Adapedonta and the divergent clade of Neoheterodontei. Neoheterodontei was comprised of Venerida and Myida, the former of which now also contains Chamidae as the sister group to all the remaining venerid taxa. Moreover, molecular divergence times were inferred by calibrating nine nodes in the Imparidentia tree of life by extinct taxa. The origin of these major clades ranged from Ordovician to Permian with the diversification through the Palaeozoic to Mesozoic. Overall, the results obtained in this study demonstrate a better-resolved Imparidentia phylogeny based on mitochondrial genomes.

Paternal genetic intergenerational and transgenerational effects of cadmium exposure on hormone synthesis disorders in progeny ovarian granulosa cells - Yi Sun; Chenyun Zhang; Lingfeng Luo; Hao Lin; Chenchen Liu; Wenchang Zhang (Environmental Pollution, 2023)

Phylogeny of Veneridae (Bivalvia) based on mitochondrial genomes - Yu Wang; Yi Yang; Hongyue Liu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Zoologica Scripta, 2021)
Veneridae is one of the most diverse families of bivalve molluscs. However, their phylogenetic relationships among subfamilies have been debated for years. To explore phylogenetic relationships of Veneridae, we sequenced 13 complete mitochondrial genome sequences from eight subfamilies and compared with available complete mitochondrial genome of other Veneridae taxa (18 previously reported sequences). Phylogenetic analyses using probabilistic methods recovered two highly supported clades. In addition, the protein‐coding gene order revealed a highly conserved pattern among the same subclade lineages. According to our molecular analyses, Tapetinae should be recognized as a valid subfamily, but the genera formed para‐polyphyletic clades. Chioninae was recovered not monophyletic that differs from a previously molecular phylogeny. Furthermore, the reconstructed chronogram calibrated with fossils recovered the Veneridae have originated during the early Permian (about 290 million years ago). Noticeably, programmed frameshift was found in the nad4 gene of Leukoma jedoensis , Anomalodiscus squamosus and Antigona lamellaris and cob gene of L. jedoensis . This is the first time that the presence of the programmed frameshift has been found in the protein‐coding genes of Heterodonta species. Our results improved the phylogenetic resolution within Veneridae, and a more taxonomic sampling analysis of the subfamily Chioninae is supposed to construct.

Mitogenomic phylogeny of Trochoidea (Gastropoda: Vetigastropoda): New insights from increased complete genomes - Erfei Guo; Yi Yang; Lingfeng Kong; Hong Yu; Shikai Liu; Zhanjiang Liu; Qi Li (Zoologica Scripta, 2021)
Increased mitochondrial (mt) genomes can provide more sets of genome‐level characteristics for resolving deeper phylogeny. Limited information with respect to the Trochoidea mitochondrial genome organization is available; besides, monophyly and internal relationships of the superfamily still remain a matter of discussion. To resolve the monophyly and internal phylogenetic controversies of Trochoidea and expand our understanding for mt genomic characteristic evolution among Trochoidea, the phylogenetic trees were reconstructed using 13 newly sequenced complete mt genomes and 35 genomes from GenBank, and both the maximum likelihood and Bayesian inference analyses were highly supported. Vetigastropoda phylogenetic analyses recovered the monophyly of Trochoidea. Trochoidea phylogenetic analyses and genetic distances supported the non‐monophyly of Tegulidae and Tegula , indicating that the taxonomic status of several genera ( Rochia , Tectus and Cittarium ) should be revised and Tegula , Omphalius and Chlorostoma should be placed as a same genus. The close affinity between Tectus virgatus and Rochia was also revealed. Three‐nucleotide insertion in nad1 , nine‐nucleotide insertion and six‐nucleotide deletion in nad5 are detected in Tegulidae, Tectus and Rochia , respectively. Gene orders within Trochoidea are stable, with gene rearrangements exclusive to tRNA genes observed. Homoplasious convergences because of trnT rearrangement display translocation in Turbinidae and reversion in Trochidae and Calliostomatida. For trnE and trnG , we identify 11 arrangement types, suggesting that the gene rearrangement history needs to be further evaluated. Our study emphasizes the importance of mt genomes in resolving phylogenetic relationships within Trochoidea. In addition, the mt genomic characters would contribute new insights into the classification of Trochoidea.

Grazing by microzooplankton and copepods on the microbial food web in spring in the southern Yellow Sea, China - Yuan Zhao; Yi Dong; Haibo Li; Shiquan Lin; Lingfeng Huang; Tian Xiao; Gerald Gregori; Li Zhao; Wuchang Zhang (Marine Life Science & Technology, 2020)
Assessment of microzooplankton and copepods grazing pressure on picoplankton is a key requirement for resolving the microbial food web efficiency. Although microzooplankton grazing on picoplankton has been extensively studied, the impact of microzooplankton on different groups of picoplankton, i.e., heterotrophic bacteria, Synechococcus and picoeukaryotes have rarely been compared. Furthermore, in the very few existing studies there is no consistent evidence of an enhancing or restraining effect of copepods on picoplankton. More studies are needed to improve our understanding of the influence of microzooplankton and copepod on picoplankton. Dilution incubations and copepod addition incubations were performed during a cruise to the southern Yellow Sea on May 16–29, 2007. The bulk grazing of microzooplankton and the calanoid copepod Calanus sinicus on phytoplankton, flagellates and picoplankton was estimated. Stations were divided into either eutrophic or oligotrophic according to the nutrient and biological parameters. Picoplankton comprised a large part of the diet of microzooplankton in the central oligotrophic area, while phytoplankton was the main food of microzooplankton in the coastal eutrophic area. In the central oligotrophic area, microzooplankton preferred grazing on Synechococcus . After copepod addition, ciliate abundance decreased while Synechococcus abundance increased (382%, 64% and 64% at three experimental stations, respectively), indicating strong grazing pressure of microzooplankton on Synechococcus . Our results suggest that Synechococcus might be an essential carbon source the planktonic food web in the oligotrophic waters of southern Yellow Sea.

Mitogenomic phylogeny of the Naticidae (Gastropoda: Littorinimorpha) reveals monophyly of the Polinicinae - Hongyue Liu; Yi Yang; Shao'e Sun; Lingfeng Kong; Qi Li (Zoologica Scripta, 2020)
The Naticidae is a species‐rich family of predatory marine gastropods with substantial interspecific morphological diversity. The classification of the Naticidae has been traditionally based on morphology data, but the phylogenetic relationships within the family are debated due to conflicting molecular results, especially regarding the monophyly of subfamilies Polinicinae and Naticinae. To further resolve the phylogenetic controversies within the Naticidae, we undertake a phylogenetic approach using 14 newly sequenced complete or nearly complete (only lacking a control region) mitochondrial genomes. Both the maximum likelihood and Bayesian inference analyses supported monophyly of the Polinicinae, but paraphyly of the Naticinae due to the placement of the enigmatic genus Notocochlis . The ancestral character reconstruction suggests that the operculum, a character that currently defines the two subfamilies, evolved from an ancestor with a calcareous operculum in the evolutionary history of naticids. In addition, the chronogram estimates that naticids was originated in late Triassic (about 227 million years ago), consistent with previous hypotheses. Our study highlights the importance of using complete mitochondrial genomes while reconstructing phylogenetic relationships within the Naticidae. The evolution scenario of the naticid operculum contributes new insights into the classification of Naticidae.

Mitogenomic phylogeny of Nassarius (Gastropoda: Neogastropoda) - Yi Yang; Qi Li; Lingfeng Kong; Hong Yu (Zoologica Scripta, 2019)
Nassariids (Family Nassariidae) are a group of marine snails that are distributed worldwide, with their maximum species diversity in tropical regions, particularly the Indo‐Pacific. However, the traditional taxonomy of Nassariidae defined by shell or radula characters is usually inconsistent with little phylogenetic signal. In the present study, the complete mitochondrial (mt) genomes of nine Nassarius species were sequenced and compared with other eight nassariid species previously reported. All nassariid mt genomes showed the same gene order as in most caenogastropods and shared a very similar pattern with respect to genome size, nucleotide composition and AT contents. A deletion of three nucleotides in nad6 gene was detected in Nassarius jacksonianus and Nassarius acuticostus , and this feature also provided implications for nassariid phylogeny. The genetic distance analysis and reconstructed phylogeny revealed a distant relationship between N . jacksonianus or N. acuticostus and other members in Nassarius . The mitogenomic phylogeny recovered the evolutionary relationships within Nassarius with high statistical support. In addition, a chronogram was reconstructed under an uncorrelated relaxed molecular clock, which dated the divergence among main lineages of Nassarius during ~31 MYA.

Phylogenetic age differences in tree assemblages across the Northern Hemisphere increase with long‐term climate stability in unstable regions - Gang Feng; Ziyu Ma; Blas M. Benito; Signe Normand; Alejandro Ordonez; Yi Jin; Lingfeng Mao; Jens‐Christian Svenning (Global Ecology and Biogeography, 2017)
Aims Long‐term climate stability is hypothesized to drive the emergence of species assemblages with large species age differences due to the accumulation of relict species and relatively newly arisen species via reduced extinction and increased speciation. Few studies have addressed these predictions and so far no study has done so for plants across the Northern Hemisphere. Here, we linked Quaternary‐scale climate variability to phylogenetic age differences between the oldest and youngest group of species in tree assemblages in 100 km × 100 km grid cells across the Northern Hemisphere to test these predictions. Location Northern Hemisphere. Methods Last Glacial Maximum (LGM)‐to‐present shifts in temperature and precipitation were used as proxies for Quaternary‐scale glacial–interglacial climate variability. Simultaneous autoregressive (SAR) models were used to assess the relationships between phylogenetic age differences and Quaternary‐scale climate variability. Results We found that phylogenetic age differences overall were largest in China and smallest in Europe, and they declined with increasing temperature instability as predicted, but only in Europe and North America. In China, the relatively mild Quaternary climate changes did not appear to have strongly affected phylogenetic age differences in tree assemblages. Main conclusions Our results show that phylogenetically diverse assemblages with large phylogenetic age differences among species are associated with relatively high long‐term climate stability, with intra‐regional links between long‐term climate variability and phylogenetic composition especially strong in the more unstable regions. These findings point to future climate change as a key risk to the preservation of the phylogenetically diverse assemblages in regions characterized by relatively high paleoclimate stability, with China as a key example.

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Cloning and Characterization of a Novel Human Prefoldin and SPEC Domain Protein Gene (PFD6L) From the Fetal Brain - Jiayi Zhang; Lingfeng Liu; Xiaomeng Zhang; Feng Jin; Jinzhong Chen; Chaoneng Ji; Shaohua Gu; Yi Xie; Yumin Mao (Biochemical Genetics, 2006)

Molecular cloning and characterization of a novel human protein phosphatase 2C cDNA (PP2C ε) - Feng Jin; Chaoneng Ji; Lingfeng Liu; Jianfeng Dai; Shaohua Gu; Xianfei Sun; Yi Xie; Yumin Mao (Molecular Biology Reports, 2004)